The Characteristics of Patients with Lymphadenopathy at Bhakti Kartini Hospital for The 2020-2022 Period - Widjaya, Raden Agil; Atamimi, Taufik Aziz; Prakoso, Adi (Syntax Literate, 2025)
Lymphadenopathy refers to the abnormal enlargement, consistency, or number of lymph nodes, with etiologies ranging from self-limited infections to malignancies. Excision biopsy of an accessible peripheral lymph node remains critical for early diagnosis and effective management. This study aimed to describe the demographic, clinical, and histopathological characteristics of patients diagnosed with lymphadenopathy at Bhakti Kartini Hospital between 2020 and 2022. A retrospective cohort study reviewed patient medical records from January to August 2023. Data were analyzed descriptively, focusing on demographic profiles, imaging findings, and histopathological results. Among 113 cases, the mean age was 25.28 years, with a predominance of women (51.3%), individuals with higher education (71.7%), students (35.4%), and unmarried individuals (54.9%). Chest X-ray results were predominantly normal (92%), and the most common site of lymphadenopathy was cervical (69.9%). Histopathological examination revealed that the majority of biopsies were benign. These findings highlight that young, educated, unmarried women represent the majority of lymphadenopathy cases in this setting, with cervical lymph node involvement and routine chest imaging being common features.